2018
DOI: 10.1038/s41431-017-0052-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of metreleptin treatment and dietary intervention with neurological outcomes in Celia’s encephalopathy

Abstract: Celia's encephalopathy (progressive encephalopathy with/without lipodystrophy, PELD) is a recessive neurodegenerative disease that is fatal in childhood. It is caused by a c.985C>T variant in the BSCL2/seipin gene that results in an aberrant seipin protein. We evaluated neurological development before and during treatment with human recombinant leptin (metreleptin) plus a dietary intervention rich in polyunsaturated fatty acids (PUFA) in the only living patient. A 7 years and 10 months old girl affected by PEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The neurological impairment remains stable. These results are in line with a previous case reported by Araújo-Vilar and colleagues, who demonstrated a clear slowdown in neurological regression with metreleptin treatment in combination with a diet rich in polyunsaturated fatty acids in a child with PELD [9].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The neurological impairment remains stable. These results are in line with a previous case reported by Araújo-Vilar and colleagues, who demonstrated a clear slowdown in neurological regression with metreleptin treatment in combination with a diet rich in polyunsaturated fatty acids in a child with PELD [9].…”
Section: Resultssupporting
confidence: 93%
“…Conditions associated with variants in the BSCL2/seipin gene include progressive encephalopathy with/without lipodystrophy (PELD), also called Celia's encephalopathy (MIM#615924) and congenital general lipodystrophy type 2 (CGL2) [2,5]. PELD is associated with BSCL2 variants that cause skipping of exon 7 and is characterized by the development of progressive myoclonic epilepsy (PME) at a young age and severe progressive neurological impairment, which is rapidly fatal in many, but not all, cases [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the patient has both phenotypes of progressive encephalopathy and lipodystrophy. Recently, it was shown that metreleptin intervention, used for lipodystrophy treatment, could help a compound heterozygous patient with PELD [ 111 ].…”
Section: Merging Of Genetic Conceptsmentioning
confidence: 99%
“…Dopaminergic Mes23.5 cell line, dopaminergic N27 cell line and SH-SY5Y cell line were cultured as previously described [2] , [3] , [4] . AngII (A9525, Sigma) was used at a concentration of 100 nM 30 min before treatment with the dopaminergic neurotoxin 6-OHDA (0.02% saline ascorbate; H4381 Sigma) when used in combination, except otherwise stated.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%